Factors related to promotion of physical activity in clinical oncology practice: A scoping review. (February 2023) - Schmidt, M.L.K.; Østergren, P.; Kvorning Ternov, K.; Sønksen, J.; Midtgaard, J.
Abstract: Objectives: To map which factors have been considered, explored, and found to influence physical activity (PA) promotion by oncology physicians and nurses (OPN). Methods: A scoping review of empirical studies was conducted using Arksey and O'Malley's framework and the PRISMA-ScR guideline. The quality of the studies was evaluated using the QATSDD tool. Results: Twenty-nine publications were included. The methodological quality of the studies was low to moderate. Studies have shown a positive attitude towards PA and recommending PA. PA knowledge seems to influence PA promotion by OPNs to some extent. Structural barriers for PA promotion are the most endorsed barriers but to what extent they influence PA promotion is unclear. The demographic and professional characteristics of OPNs and their PA behavior do not seem to influence PA promotion to a greater extent. Patients' PA interest, health characteristics, and medical conditions are additional factors. Their implications for PA promotion are not fully elucidated. Conclusions: The varied results across the studies, together with the methodological limitations of the studies, make it unclear to what extent the explored factors influence PA promotion by OPNs. Practice Implications: More research into what influences OPNs' engagement in PA promotion is warranted to support clinical PA promotion. Highlights: Physicians and nurses are in a favorable position to promote physical activity (PA). Knowledge of PA benefits positively influences PA promotion to some extent. Lack of time and knowledge are frequently reported barriers for PA promotion. Clinicians' own PA behavior and demographics do not seem to influence PA promotion. More research is needed to better understand the factors' impact on PA promotion.